Pilar dan Karakteristik Pasar Dalam Ekonomi Islam - Farid Fathony Ashal (Islamic Economics Journal, 2020)
This article aims to examine the concept of the market in Islamic literature that had been practised by the classical period. The method used in this study is qualitative research with a literature study approach. The results of this study proved that Islamic literature had provided the application of market concepts which include pillars and characteristics as signs in market management, price mechanism, and avoiding from usury, gharar, maisir. The well functioning of the market has an important role in human life, yet that Islamic doctrine provided the constructive rules as an effort to purify the process of transferring property and goods from just and civilized public relations.